2017
DOI: 10.1515/aoas-2016-0020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Polymorphism in IGF-I and IGFB-3 Genes and their Relationship tith Twinning Rate and Growth Traits in Markhoz Goats

Abstract: growth rate and twinning rate are economic traits that can be used in goat breeding objectives. the aim of this study was to investigate polymorphisms in the insulin-like growth factor 1(IGF-I) and insulin-like growth factor binding protein (IGFBP-3) genes and their relationship with growth traits and twinning in Markhoz goats. Two sets of specific primers were used to amplify a 249bp fragment of IGF-I gene and a 316bp fragment of IGFBP-3 gene. pCr-ssCp analysis revealed three banding patterns for each gene th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…Recent studies have reported an association between SNPs in IGFBP-3 gene with the economic trait on ruminant livestock, including significantly correlated to the birth weight, the body weight of 12, 18 and 24 months (Choudhary et al 2007), weaning weight and ADG from birth to weaning (Rasouli et al 2016), the chest width and chest circumference (Gao et al 2009), and the differences in serum concentrations of IGFBP-3 as a result of the SNP (Choudhary et al 2006). This is due to the significance of IGFBP-3 in the IGF-I regulation; they regulate the amount of the IGF-I to their receptors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have reported an association between SNPs in IGFBP-3 gene with the economic trait on ruminant livestock, including significantly correlated to the birth weight, the body weight of 12, 18 and 24 months (Choudhary et al 2007), weaning weight and ADG from birth to weaning (Rasouli et al 2016), the chest width and chest circumference (Gao et al 2009), and the differences in serum concentrations of IGFBP-3 as a result of the SNP (Choudhary et al 2006). This is due to the significance of IGFBP-3 in the IGF-I regulation; they regulate the amount of the IGF-I to their receptors.…”
Section: Resultsmentioning
confidence: 99%
“…Eight SNPs have been detected in exon 2 of IGFBP-3 gene, 6 of them produce nonsynonymous protein coding or non-synonymous mutation (Sharma et al 2014) which can lead to a significant metabolic abnormality that is desirable or not desirable (Veneroni-Gouveia et al 2015;de Camargo et al 2015). IGFBP-3 gene expression was higher in the liver and longisimus dorsi muscles, thus contributing to the development of these organs (Zhang et al 2015), increased ADG from birth to weaning and weaning weight (Rasouli et al 2016), but there is not enough evidence to suggest that SNPs are associated with milk production (Zhou et al 2016).…”
Section: B I O D I V E R S I T a S 18 (2): 795-800 April 2017 798mentioning
confidence: 99%
See 2 more Smart Citations
“…It seems that a study on major genes known for the twining trait can distinguish S subpopulations from T subpopulations. For example, Rasouli et al (2016) reported that the twinning rate in Markhoz goats was significantly influenced by the IGF-I and IGFBP-3 genotypes; also, the association of two single nucleotide polymorphisms (SNPs) in the growth hormone (GH) gene with the litter size and superovulation response in goat breeds has been studied, and the results have shown that the two loci of the GH gene are highly associated with abundant prolificacy and a superovulation response in goat breeds (Zhang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%